2018
DOI: 10.3906/sag-1803-201
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of combined use of alloplastic-based tricalcium phosphate bone graft and antihemorrhagic plant extract (ABS) on bone regeneration in surgically induced bone defects in nondiabetic rats: an experimental animal study

Abstract: Introduction Periodontal disease is an infectious disease with a complex pathogenesis characterized by periodontal tissue and bone loss, in which local factors, host response, environmental factors, and genetic predisposition play important roles in etiology (1). The inflammation occurring during the development of a periodontal disease may result in degeneration of bone tissue causing changes in bone morphology (2). However, in periodontal defects, various graft materials are used to remove deformities caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…They found that both β-TCP and ABS had positive histological and radiological effects on wound healing and bone formation in samples taken on day 56 after surgery [29]. In the first macroscopic examination we observed in our study, it was determined that the group with the closest appearance of scar tissue to normal structure was group with application of ABS hemostat, suggesting a positive effect of ABS hemostat on wound healing.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…They found that both β-TCP and ABS had positive histological and radiological effects on wound healing and bone formation in samples taken on day 56 after surgery [29]. In the first macroscopic examination we observed in our study, it was determined that the group with the closest appearance of scar tissue to normal structure was group with application of ABS hemostat, suggesting a positive effect of ABS hemostat on wound healing.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, Kuruoğlu et al (2017) evaluated the late effects of the combination of ABS and β-tricalcium phosphate (TCP) using immunohistochemical methods and they found the bone healing effects of ABS hemostat in their study [17]. Afterwards, Tanık et al (2018) also investigated the late period effects of the combination of ABS and β-TCP on the regeneration of bone tissue in rats [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABS has also been shown to be useful for local hemostasis, wound healing, and infection control in dental surgery (Ercetin et al., 2010). Although ABS was originally produced as a hemostatic agent, it has also been reported to promote bone tissue healing through angiogenic and cell proliferation mechanisms (Bilgili et al., 2010; İşler et al., 2010; Şimşek et al., 2013; Tanik et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have evaluated the benefits of ABS for bone healing (İşler et al., 2010; Pamuk et al., 2016; Şimşek et al., 2013; Tanik et al., 2018), to our knowledge there is no study that used this agent for periodontal regenerative therapy. Our hypothesis is ABS may have a positive impact on the regeneration of experimentally created periodontal defects through its angiogenic and cell proliferation‐promoting properties.…”
Section: Introductionmentioning
confidence: 99%